2019
DOI: 10.1088/1742-6596/1382/1/012124
|View full text |Cite
|
Sign up to set email alerts
|

On the possibility to improve heat transfer of a sphere by natural convection and water mist

Abstract: This paper aims to evaluate the effects of water mist on steady natural convection heat transfer from a sphere. Experimental investigations were performed for the Nusselt number (Nu) under a range of water mist concentration in both cases, sphere located in an open volume space with constant surrounding temperature and inside a cylindrical channel with sphere-to-channel diameter ratio (d/D=0.73). The results obtained from the related experimental work indicated that the heat transfer rate was enhanced over tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…The intensification of heat transfer by water drops can include four main physical processes [16,17]: evaporation of water microdroplets on the surface of cylinders, evaporation of a water film on the surface of cylinders, convective heat transfer, and a decrease in air temperature due to an increase in its humidity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The intensification of heat transfer by water drops can include four main physical processes [16,17]: evaporation of water microdroplets on the surface of cylinders, evaporation of a water film on the surface of cylinders, convective heat transfer, and a decrease in air temperature due to an increase in its humidity.…”
Section: Resultsmentioning
confidence: 99%
“…While analyzing the heat exchange between the flow of fine-air water mist and the heated surface, it is usually considered the total quantity of heat which is transferred by the air and water mixture, and the heat which is expended for the water heating and evaporation [16,17]:…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This phenomenon is one of the typesof thermal transfer and it was found that there are many works that focus on the study of the heat transfer by natural convection of fluid flow due to a sphere under various physical conditions. Recently, Abed et al [10] estimated the water mist impacts enhance the heat transfer with natural convection around the sphere. A numerical study of natural convection boundary layer flow of Carreau non-Newtonian fluid over an isothermal sphere in the presence of a magnetic field with slip and jump conditions has been prepared by Amanulla et al [11] .…”
Section: Introductionmentioning
confidence: 99%
“…In this study, a water droplet cooling technique or (water mist cooling technique) were developed by suspending fine water droplets into the working fluid. The water mist techniques, not a new cooling concept and has been successfully applied in many industrial applications [13][14][15][16][17][18]. Utilizing water mist as a cooling medium provides excellent cooling approaches to dissipate heat even larger than the single-phase air cooling approaches.…”
Section: Introductionmentioning
confidence: 99%